2021
DOI: 10.1088/1674-4527/21/10/251
|View full text |Cite
|
Sign up to set email alerts
|

An Arecibo follow-up study of seven pulsars discovered by Five-hundred-meter Aperture Spherical radio Telescope (FAST)

Abstract: We present Arecibo 327 MHz confirmation and follow-up studies of seven new pulsars discovered by the Five-hundred-meter Aperture Spherical radio Telescope (FAST). These pulsars are discovered in a pilot program of the Commensal Radio Astronomy FAST Survey (CRAFTS) with the ultra-wide-bandwidth commissioning receiver. Five of them are normal pulsars and two are extreme nulling slow pulsars. PSR J2111+2132’s dispersion measure(DM: 78.5 pc cm−3) is above the upper limits of the two Galactic free electron density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Cruces et al 2021 presented confirmation and timing results of 10 CRAFTS pulsars, including 9 isolated pulsars and 1 neutron star -Carbon-Oxygen white dwarf (WD) binary system, with the 100-m Effelsberg radio-telescope. Wang et al 2021a showed con- firmation results and nulling studies of 7 CRAFTS pulsars with the Arecibo 305-m Telescope.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Cruces et al 2021 presented confirmation and timing results of 10 CRAFTS pulsars, including 9 isolated pulsars and 1 neutron star -Carbon-Oxygen white dwarf (WD) binary system, with the 100-m Effelsberg radio-telescope. Wang et al 2021a showed con- firmation results and nulling studies of 7 CRAFTS pulsars with the Arecibo 305-m Telescope.…”
Section: Introductionmentioning
confidence: 73%
“…The ongoing surveys, such as the CRAFTS and the FAST Galactic Plane Pulsar Snapshot Survey (Han et al 2021, GPPS) are expected to discover many more MSPs, and thus make a significant contribution to the PTA experiments. Until December 2021, combining all pulsars discovered in the CRAFTS and the early FAST commission survey, more than 160 new pulsars 3 (include 35 MSPs) (Qian et al 2019;Zhang et al 2019;Cameron et al 2020;Wang et al 2021a;Cruces et al 2021;Wang et al 2021c), 4 FRBs (Zhu et al 2020;Niu et al 2021) and 1 radio-faint MSP from the Fermi-LAT unassociated source (Wang et al 2021b;You et al 2021) have been discovered in total ∼ 850 hours. The area searched represents 15% of the sky that FAST can see.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using GSP pipeline, we discovered 13 new pulsars 6 as shown in Table 6, and used FFA (Staelin 1969) for periodical search. For the single pulses adjacent to the DM, the maximum range of the FFA search is 1.5 times the time interval of the two single pulses adjacent to the DM; the follow-up timing observation has been completed by Prakes and Effelsberg Radio Telescope, these pulsars have been reported upon (Cameron et al 2020;Qian et al 2019;Zhang et al 2019) and (Cruces 2021 MNRAS accepted, Wang Shen (Wang et al 2021))), the discovery plots of GSP for each of 13 pulsars are shown in Figure 6. -GSP implement the presto dedispersion package 'prepsubband' with CUDA, which was shown to be ∼120 times faster than the original 'prepsubband' and ∼60 times faster than the MPI version for processing CRAFTS data.…”
Section: Discovery Of 13 Pulsars From Crafts Surveymentioning
confidence: 99%
“…RRAT J1918−0449 is the first RRAT discovered in the commensal radio astronomy FAST survey (CRAFTS; 12 Nan et al 2011;Li et al 2018;Qian et al 2019;Zhang et al 2019;Cameron et al 2020;Wang et al 2021aWang et al , 2021bCruces et al 2021) using a single-pulse search technique (Zhu et al 2014). In this paper, we present the discovery and analysis of the intriguing emission behavior of RRAT J1918−0449 observed with the FAST, which is organized as follows.…”
Section: Introductionmentioning
confidence: 96%